PERKEMBANGAN PENGUNJUNG PERPUSTAKAAN UMUM - Riani Riani; Muhamad Nuryadi, Ana Mahdalena, Achmad Al Farisi, Muhammad Samudra, Riza Fahlapi (CV. ADIBA AISHA AMIRA, 2025)
Reading is one of the factors to improve one's quality but unfortunately according to survey research conducted by the Programme for International Student Assessment (PISA) released by the Organisation for Econoic Co-operation and Development (OECD) in 2019 Indonesia still ranks in the top 10 from the bottom for low literacy levels and interest in reading. Considering this, it makes us realise how important institutions such as libraries are in the community. The library's contribution to increasing people's interest in reading is in the form of providing reading materials and providing adequate facilities. Public libraries as a source of information and knowledge have an important role in educating the nation's life. One of the indicators of library progress is the level of community visits, this study aims to analyse the development of public library visitors within a certain period of time. The method used in this research is to collect data from various sources such as journals, scientific articles, and official reports. The data was analysed descriptively to describe the development trend of public library visitors. This paper will discuss the development of library visitors from various categories of visitors described in tables, diagrams and several measures in statistics.